A efetivação do direito humano à paz por intermédio da Defensoria Pública: atuação em favor da vítima na presecução penal - Dantas Junior, Genival Torres [UNESP] (2014)
The present study aims to analyse the implementation of the human right to peace through the public defender's Office, with regard, specifically, to the victim's tutelage under criminal procedure. Initially, general ideas are worked on human rights and after, analyzes the process of internationalization of the copyright, its concept, characteristics and its dimensions. In a second moment, will be studied the human right to peace, identifying the legislation that he reference, highlighting its collective and individual dimension and, still, its contents, the possibilities of violation and the extent to which it belongs, clarifying the relationship between the right to peace and the rights of the victim in criminal prosecution. After an approach was held on the role of the victim in the criminal process, making an analysis of the concept of victim, the historical evolution and the current context of the participation of the victim in criminal investigations and in criminal proceedings, the protection of their rights and their protection. After, we analyzed the legal institution public defender, its origins, evolution and legislation that regulate them, their duties to meet essential needs and your goals. Then it was examined how the public defender may be one of the means of implementation of the human right to peace, specifically in relation to the victim, under criminal procedure. Make mention of the role of the Public Defender's Office on behalf of the offended us criminal and special courts in favor of the woman who suffers domestic violence and family. Still, take care of the Public Defender's Office's role in the protection of child, adolescent and elderly victims of crime, in addition to people with disabilities in these conditions and offended. Finally, it is the function of the Public Defender's Office in safeguarding the rights of the victim of crime. The work uses as a method of the...